Chemoradiotherapy followed by continued immunotherapy for out-of-field progression during consolidation in limited-stage SCLC: a case report - Jiang, Ying; Tong, Xu; Bi, Nan (Frontiers in Immunology, 2025)
BackgroundWhile consolidation immunotherapy after chemoradiotherapy (CRT) improves survival in limited-stage small cell lung cancer (LS-SCLC), some patients develop out-of-field progression during consolidation. Optimal management in such cases remains undefined.Case presentationWe describe a 49-year-old male with LS-SCLC who developed supraclavicular lymph node metastasis during consolidation immunotherapy following definitive CRT. The patient underwent concurrent chemoradiotherapy targeting the recurrent node, followed by continued consolidative immunotherapy. This approach led to complete response of both the primary tumor and the metastatic lymph node, with minimal toxicity.ConclusionThis case highlights the potential role of combining salvage radiotherapy with continued immunotherapy in managing isolated nodal recurrence during consolidation. Further studies are warranted to validate this individualized strategy.